2012
DOI: 10.1038/onc.2011.580
|View full text |Cite
|
Sign up to set email alerts
|

Dickkopf 4 (DKK4) acts on Wnt/β-catenin pathway by influencing β-catenin in hepatocellular carcinoma

Abstract: Deregulation of Wnt/b-catenin pathway is a hallmark of major gastrointestinal cancers including hepatocellular carcinoma (HCC). The oncogenic role of b-catenin is well defined but reasons for its accumulation in HCC remain unclear. Dickkopf 4 (DKK4) acts as a negative regulator of Wnt/b-catenin pathway but its functional role in liver carcinogenesis has not been studied. We investigated the role of DKK4 in b-catenin regulation in HCC. Reduced expression of DKK4 was found in 47% (38/81) of HCC, as measured by q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
66
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(71 citation statements)
references
References 70 publications
5
66
0
Order By: Relevance
“…However, in the study by Fatima et al (25), the expression levels of DKK4 β-catenin and cyclin D1 were decreased in hepatoma carcinoma cells, and β-catenin was accumulated in the cytoplasm. Similar results have been observed in colorectal cancer (32).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…However, in the study by Fatima et al (25), the expression levels of DKK4 β-catenin and cyclin D1 were decreased in hepatoma carcinoma cells, and β-catenin was accumulated in the cytoplasm. Similar results have been observed in colorectal cancer (32).…”
Section: Discussionmentioning
confidence: 94%
“…The neoplasm incidence rate was 100%, and the tumor weights of the mice implanted with cells overexpressing DKK4 were significantly higher than those of the control mice implanted with an empty vector. DKK4 is considered to inhibit the development of tumors, as an antagonist of the Wnt pathway and has also been reported to be able to inhibit the proliferation of tumor cells in hepatic carcinomas (25). However, the issue of whether DKK4 acts as a tumor inhibitor or promoter remains to be resolved.…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemical data linked decreased Dkk4 expression to accumulation of β-catenin in hepatocellular carcinoma tissue. In addition, the authors showed that Dkk4 overexpression in hepatocellular carcinoma cell lines resulted in reduced cell proliferation, colony formation and cell migration, suggesting a tumour-suppressive role for Dkk4 (74). A recent study demonstrated that hepatocellular carcinoma cells proliferate upon stimulation in high glucose conditions as a result of Dkk4 downregulation, allowing Wnt3a-mediated β-catenin signalling and c-Myc upregulation (75), suggesting the Wnt pathway may be a therapeutic target in insulin-resistant conditions, leading to hepatocellular carcinoma.…”
Section: Wnt/β-catenin Signalling and Cancermentioning
confidence: 99%
“…A scratch was then created in each assayed well as described (9,19). Extent of cell migration towards the created wound was followed on every 12 h till 36 h.…”
Section: Role Of Asb4 In Conferring Migration and Invasion Propertiesmentioning
confidence: 99%
“…Lipofectamine 2000 was used as transfecting agent. After 48 h, cells were harvested and suspended in Reporter Lysis Buffer (Promega) and subjected to dual luciferase reporter assay as before (18,19).…”
Section: Luciferase Reporter Assay To Examine the Binding Of Mir-200amentioning
confidence: 99%